Challenges in classifying human chromosomal heteromorphisms using banding cytogenetics: From controversial guidelines to the need for a universal scoring system - Sílvia Pires; Paula Jorge; Thomas Liehr; Natália Oliva-Teles (Human Genome Variation)
Abstract Chromosomal heteromorphisms (CHs) are morphological variations predominantly found in constitutive heterochromatic regions of the genome, primarily composed of tandemly repetitive sequences of satellite DNA. Although not completely devoid of genes, these regions are typically not transcribed into proteins and lack obvious phenotypic impact. Nonetheless, their clinical importance is increasingly under scrutiny, with several studies aiming to assess their influence on human diseases and susceptibilities, especially as they are seemingly part of the long noncoding RNAs in certain tissues. This article summarizes the classification methods of human heterochromatic CHs documented in the literature over the last two decades. Multiple scoring systems have been identified, and previous approaches for CH assessment and reporting in genetic diagnosis have shown inconsistencies. Owing to the current heterogeneity in the classification of CHs, data analysis may be biased, impacting the quality of clinical reports and human genetic research. This review highlights the need for a universal scoring system, which is essential for scientific reproducibility and the accurate identification and clinical evaluation of human CHs.